COVID-19 healthcare and social-related needs from the perspective of Spanish patients and healthcare providers: a qualitative analysis of responses to open-ended questions - Andrea Duarte-Díaz; Andrea Duarte-Díaz; Mariana Aparicio Betancourt; Mariana Aparicio Betancourt; Laura Seils; Carola Orrego; Carola Orrego; Carola Orrego; Lilisbeth Perestelo-Pérez; Lilisbeth Perestelo-Pérez; Jaime Barrio-Cortes; Jaime Barrio-Cortes; et al. (Frontiers in Public Health, 2023)
IntroductionIdentifying stakeholders’ needs is crucial to informing decisions and policy development. This study aims to identify healthcare and social-related needs and effective strategies associated with COVID-19 from the first-person perspectives of patients and healthcare providers.MethodsCross-sectional online survey design including qualitative open-ended questions, conducted in primary care and hospital settings across Spain, with 12 out of 19 regions represented. Adults aged 18 years and older, who (a) resided in Spain and had a history of COVID-19 or (b) worked as healthcare providers delivering direct or indirect care for people with COVID-19 in Spanish primary care or hospitals during 2020 were eligible to participate. Recruitment was conducted via social-media networks (Twitter, LinkedIn, and WhatsApp) and communication channels of key organizations including patient and professional associations and groups. A total of 182 people were invited to complete the surveys and 76 people completed the surveys (71% women), of which 33 were home-isolated patients, 14 were hospitalized patients, 16 were primary care professionals, and 13 were hospital care professionals.ResultsA total of 327 needs and 86 effective strategies and positive aspects were identified across surveys and classified into the following overarching themes: (i) Accessibility, (ii) Basic needs, (iii) Clinical care, (iv) Person-and-family centered care, (v) Caring for the healthcare professional, (vi) Protocolization, information, health campaigns, and education, (vii) Resource availability, (viii) and Organizational needs/strategies.DiscussionFindings indicate the Spanish health and social care systems were generally unprepared to combat COVID-19. Implications for research, practice, and policy focus on integrating first-person perspectives as best practice to identify, prioritize and address needs to increase health and social care systems capacity and preparedness, as well as providing well-co-coordinated responses across government, healthcare, and non-government sectors to promote and protect the physical and mental health of all.